Analysis of E-Learning Activities as School Learning Media in the Era of Society 5.0 Using Big Data - Irika Widiasanti; Dea Astriani; Asyifa Eka Rahayanti; Bagus Septianto; Linda Widianingsih (research, training and philanthropy institution Natural Aceh, 2023)
To prepare the community to face Society 5.0, cooperation is needed from various parties, including the education sector. The development of the education sector is crucial today, as it provides optimal and quality educational services and facilitates technological advancements. Regarding educational technology, a system utilized to support learning and achieve desired outcomes, it is important to associate it with the Society 5.0 era. One form of technological development in education that can be used as a learning medium is e-learning. This research adopts a quantitative approach. The research subjects consist of secondary data from a Kaggle dataset titled